Remediation of Arsenic-Contaminated Soil Using Alkaline Extractable Organic Carbon Solution Prepared from Wine-Processing Waste Sludge. Issue 6 (18th August 2017) - Lin, Kao-Yung; Chen, Yueh-Min; Chen, Lih-Fu; Wang, Ming-Kuang; Liu, Cheng-Chung
ABSTRACT: Past studies have shown that dissolved organic carbon (DOC) washing can effectively remove heavy metals from contaminated soil. In this study, we used alkaline DOC solutions for remediation of arsenic (As)-contaminated soil (with an initial As concentration in the topsoil of 390 mg kg −1 ). The removal of As and the change in soil nutrients during DOC washing were studied for 60 min at pH 10 with a 60:1 liquid/soil ratio (v/m). Approximately 88% of As was removed by washing the soil twice using a 3000 mg L −1 DOC solution at 25°C. Following this treatment, the pH of the soil had increased from 5.6 to 9.2; organic carbon content had increased from 3.5% to 4.1%; cation exchange capacity, ammonium-N, and available phosphorus had increased to 2.3, 1.4, and 6.6 times their original levels, respectively; and exchangeable K, Na, Ca, and Mg had increased to 91, 6.1, 4.2, and 2.2 times their original levels, respectively. A sequential extraction investigation revealed that residual As and easily exchangeable As in the fraction were initially 10.2% and 9.2%, respectively, but that the former became the maximum remainder (64%) after the ultimate DOC washing.